NODAL and SHH dose-dependent double inhibition promotes an HPE-like phenotype in chick embryos - Sandra Mercier; Véronique David; Leslie Ratié; Isabelle Gicquel; Sylvie Odent; Valérie Dupé (The Company of Biologists, 2013)
SUMMARY Holoprosencephaly (HPE) is a common congenital defect that results from failed or incomplete forebrain cleavage. HPE is characterized by a wide clinical spectrum, with inter- and intrafamilial variability. This heterogeneity is not well understood and it has been suggested that HPE involves a combination of multiple gene mutations. In this model, several mutated alleles or modifying factors are presumed to act in synergy to cause and determine the severity of HPE. This could explain the various clinical phenotypes. Screening for HPE-associated genes in humans suggests the involvement of NODAL or SHH signaling, or both. To test this multigenic hypothesis, we investigated the effects of chemical inhibition of these two main HPE signaling pathways in a chick embryo model. SB-505124, a selective inhibitor of transforming growth factor-B type I receptors was used to inhibit the NODAL pathway. Cyclopamine was used to inhibit the SHH pathway. We report that both inhibitors caused HPE-like defects that were dependent on the drug concentration and on the developmental stage at the time of treatment. We also investigated double inhibition of NODAL and SHH pathways from the onset of gastrulation by using subthreshold inhibitor concentrations. The inhibitors of the NODAL and SHH pathways, even at low concentration, acted synergistically to promote an HPE-like phenotype. These findings support the view that genetic heterogeneity is important in the etiology of HPE and may contribute to the phenotypic variability.